IMPACT OF DIGITAL MARKETING, DIGITAL FINANCE, AND DIGITAL LITERACY ON BUSINESS PERFORMANCE SMEs - Bothy Dewandaru; Manuel Goncalves; Afif Nur Rahmadi (Bajang Institute, 2023)
The development of digital technology is very helpful for the community of SMEs players in an effort to expand their market reach quickly without having to meet customers directly. The digital economy era has an impact on changes in people's lifestyles, including the transaction methods used by the public.This study aims to determine the effect of digital marketing, digital finance, and digital literacy on the performance of SMEs. This research is a quantitative study with the sample being SMEs in Kediri that use marketing technology and financial technology. the results of this study indicate that digital marketing and digital literacy affect the performance of SMEs, while digital finance has no effect on the performance of SMEs